Evaluation of methods for the dissolution of Monte Fresco phosphate rock (Bioagro, 2018)
The objective of this work was to study the dissolution of the phosphate rock (PR) Monte Fresco in three Venezuelan soils with physicochemical and mineralogical characteristics that contrast in their ability to interact with the PR. The quantification of the dissolution of the PR was conducted through a comparative evaluation of four different extraction methods, widely used in experiments with PR: Olsen method, Bray I, extraction with NaOH and the impregnated filter paper method (IP). The soils were fertilized with 300 mg·kg-1 of PR. Subsequently, soil samples (triplicate) were incubated with high moisture and 25° C for 30 days. Later, treated samples were extracted with the methods above mentioned and the P in solution was determined. The same procedure was performed to soil samples without fertilizer (control). The difference between the P extracted from the treated soil and control corresponded to the dissolved P (ΔP) of the PR Monte Fresco. Although in most situation the different methods allowed the quantification of important values of dissolution of the PR Monte Fresco, we recommend the use of Olsen and Bray I, by economic and simplicity of their procedures; it is possible to use also the IP method; however, this method is less simple than the other two, involving a long time of agitation and subsequent desorption of P adsorbed on the filter paper; the NaOH method is discarded by the problems associated with the dissolution of the apatite directly from the PR without reacting with the soil.
Keywords: Acid soils; Bray I; P adsorption; solubilization